Teoria e prática no serviço social: subsídios para a reflexão sobre o exercício profissional do assistente social - Silva, Tatiana Freire da [UNESP] (2013)
Nowadays there are numerous challenges to the Social Services that end up limiting and preventing the professional social worker. Under this assumption and, using a critical perspective and all, we seek to identify what are the contradictions and challenges for the development of the professional practice of social workers in the Department of Social Development and Citizenship of the Municipality of Sertãozinho / SP, based on the theoretical and methodological, technical, operational and ethical-political Social Service, this intervention is necessary to be done by a qualified and differentiated professional of merely philanthropic and welfare actions. Thus, the work presented discussed with social workers, which is the conception of theory and professional practice, analyzed the apprehension of professionals about the dichotomy / gap between theory and practice and investigated the strategies created by these social workers to overcome the challenges found. Consider the historical of the profession and the Brazilian Social Policy in political, economic and social, which ends up establishing the material basis of the work of this professional, although this has a relative autonomy in the performance of their duties. We point so that this occupation category is significant to have clarity approaching the theoretical framework of the profession and ethical-political action as necessary instruments for the social worker, capable of mediating between theory and practice